2017
DOI: 10.1007/7651_2017_84
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Autophagy and Epithelial to Mesenchymal Transition in the Non-small Cell Lung Cancer Cells

Abstract: Autophagy is increasingly identified as a central player in many cellular activities from cell proliferation to cell division, migration, and differentiation. However, it is also considered as a double-edged sword in cancer biology which either promotes oncogenesis/invasion or sensitizes the tumor cells to chemotherapy induced apoptosis. Recent investigations have provided direct evidence for regulation of cellular phenotype via autophagy pathway. One of the most important types of phenotype conversion is Epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…This work clearly supports the published literature on the kidney, liver, and other organs, where it has been shown that autophagy regulates tissue fibrosis (32,33). However, it was recently reported that autophagy is a necessary mechanism for changing the phenotype of lung epithelial cells to mesenchymal cells (34,35); therefore, the present finding that shows incidence of autophagy in the epithelium of patients with asthma and HDM-challenged mice might confirm the role of EMT in the accumulation of mesenchymal cells in asthma pathogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…This work clearly supports the published literature on the kidney, liver, and other organs, where it has been shown that autophagy regulates tissue fibrosis (32,33). However, it was recently reported that autophagy is a necessary mechanism for changing the phenotype of lung epithelial cells to mesenchymal cells (34,35); therefore, the present finding that shows incidence of autophagy in the epithelium of patients with asthma and HDM-challenged mice might confirm the role of EMT in the accumulation of mesenchymal cells in asthma pathogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Autophagy degrades damaged organelles and allows misfolded proteins to be recycled in response to cellular stress and starvation, thereby suppressing tumor development in the early stages of cancers, whereas it improves tumor progression at advanced stages of tumor development via inducing resistance to chemotherapeutic agents [ 24 , 25 , 26 , 27 , 28 ]. The UPR is also activated in response to the accumulation of unfolded proteins in the ER [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is involved in a variety of physiological processes including cell differentiation and development, starvation and degradation of aberrant structures which ultimately maintains essential cellular homeostasis [62,63]. Physiologic autophagy plays beneficial roles on several basal cellular mechanisms in different organs through its intracellular catabolism activities, while pathological autophagy influences outcomes in disorders such as neurodegeneration, immunity, and cancer [59,[64][65][66][67][68][69]. Historically, research in the autophagy field was initiated by studies which characterized the lysosome; this led to our current knowledge about regulatory and molecular aspects of autophagy [70].…”
Section: Autophagymentioning
confidence: 99%
“…Macroautophagy was discovered in the late 1950s using morphological techniques [81]. Being a principle degrading mechanism of the cell, macroautophagy contributes to the survival of cells under stressful conditions [69,82]. Briefly, the cargo is sequestered into autophagosomes followed by their delivery to lysosomes for degradation [15].…”
Section: Macroautophagymentioning
confidence: 99%